Pengaruh Transfer Pricing, Good Corporate Governance, Growth Opportunity Terhadap Agresivitas Pajak dengan Corporate Social Responsibility Sebagai Variabel Moderasi: Penelitian - Samino Hendrianto; Nursimah Dara; Masturo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the influence of transfer pricing, good corporate governance (GCG), and growth opportunity on tax aggressiveness with corporate social responsibility as a moderation variable in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2020-2024 period. The research method used was descriptive quantitative with secondary data in the form of financial statements and sustainability reports from 10 companies taken through purposive sampling from a population of 95 companies. The data analysis method in this study is assisted by using Microsoft Office Excel and statistical software, namely Eviews 12. The research method used in this analysis is the common effect model. The results of the analysis show that transfer pricing has an effect on tax aggressiveness, while good corporate governance and growth opportunities have no effect on tax aggressiveness. Corporate Social Responsibility can moderate transfer pricing against tax aggressiveness. However, corporate social responsibility cannot moderate good corporate governance and growth opportunities against tax aggressiveness.